Treatment of Osteochondritis Dissecans of the Talus in Skeletally Immature Population: A Critical Analysis of the Available Evidence. Issue 3 (June 2016) - Buda, Roberto; Pagliazzi, Gherardo; Castagnini, Francesco; Cavallo, Marco; Giannini, Sandro
Juvenile osteochondritis dissecans of the talus (JOCDT) is a subchondral bone alteration and a partially or completely detached osteochondral fragment, affecting skeletally immature patients. A review of the English literature on PubMed was conducted. Conservative treatment was applied in patients up to Berndt-Harty stage III. Surgical indications were conservative management failure and loose bodies. The most performed procedures were drilling, subchondral bone grafting, fragment fixation, or excision. High rate of clinical success were achieved, whereas radiographic results were much lower. None of the surgical options demonstrated to be superior. Future long-term qualitative studies focusing on chondral tissue restoration are needed. Levels of Evidence: Therapeutic, Level IV